2010
DOI: 10.1007/s00348-010-1022-x
|View full text |Cite
|
Sign up to set email alerts
|

High-speed laser diagnostics for the study of flame dynamics in a lean premixed gas turbine model combustor

Abstract: A series of measurements was performed on two technically-premixed, swirl-stabilized methaneair flames (at overall equivalence ratios of  = 0.73 and 0.83) in an optically accessible gas turbine model combustor. The primary diagnostics used were combined planar laser-induced fluorescence (PLIF) of the OH radical and stereoscopic particle image velocimetry (PIV) with simultaneous repetition rates of 10 kHz and a measurement duration of 0.8 seconds. Also measured were acoustic pulsations and OH chemiluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 37 publications
8
49
0
Order By: Relevance
“…These studies also show that the flame's heat release changes the density and velocity fields, altering the hydrodynamic stability of the flow, in many cases suppressing the m = 1 instability and hence the precessing vortex core. This concurs with experiments and large-eddy simulations (LES) of swirling premixed lifted flames (Giauque et al 2005;Roux et al 2005;Boxx et al 2012).…”
supporting
confidence: 84%
“…These studies also show that the flame's heat release changes the density and velocity fields, altering the hydrodynamic stability of the flow, in many cases suppressing the m = 1 instability and hence the precessing vortex core. This concurs with experiments and large-eddy simulations (LES) of swirling premixed lifted flames (Giauque et al 2005;Roux et al 2005;Boxx et al 2012).…”
supporting
confidence: 84%
“…This frequency could be due to the existence of periodic flow structure but requires further detailed analysis of the flow field, and hence will be investigated in a later study. The trends presented in Figure 3 are similar to what Boxx et al (2012) have reported in investigation of flames with and without strong thermo-acoustic pulsations.…”
Section: Flame Characterizationsupporting
confidence: 88%
“…Similar suppression effect of combustion on PVC instability was observed in some research [42,43]. More studies indicated that the PVC occurrence and amplitude under the combustion conditions strongly depended on the operating conditions, e.g., equivalence ratios and the confinement levels [44,45]. The effects of equivalence ratio and fuel composition were examined in the current study.…”
Section: Identification Of Precessing Vortex Core By Pod Analysismentioning
confidence: 64%